PARTISIPASI KOMUNITAS PEDESAAN LAMPUNG DALAM PENGEMBANGAN MASYARAKAT - Zamhariri, Zamhariri (BINA' AL-UMMAH, 2015)
This study examines community development program, i.e. TPK PNPM Mandiri in Kota Agung village and shows that level of community members’ participation differs according to their capacity. In general, community members participate by giving contribution in the form of money, wealth, power, skills, and idea. However, participation by giving ideas to the program is considered low. In terms of implementation, community participation is signified by working together (gotong royong) in implementing certain development programs. Likewise, community also involves in program monitoring and evaluation.